The Role of Technological Change in the Evolution of the Employment to Output Elasticity - Pablo Egana-delSol; Alejandro Micco (Institute of Labor Economics (IZA), 2024)
The employment to output elasticity has risen from 0.65 during the 1960s and 1970s to 1.25 in the last two decades. We study the role of recent technological change in the evolution of this elasticity along the business cycle. Using the Covid-19-induced shock and an instrumental variable approach as sources of identification, we find that recent technologies augment the employment to output elasticity. We find that employment in sectors characterized with occupations with a high risk of automation are the most affected and that this effect is larger in sectors that have undergone a technology-capital deepening process in the last decades.
Keywords: O33; E32; J23; 330; technological change; automation; employment to output elasticity; labor markets